Pengaruh Pertumbuhan Penjualan dan Debt to Equity Ratio Terhadap Kinerja Keuangan Sektor Transportasi dan Logistik - Kholifatun Nisa; Sri Wahyuni Jamal; Muhammad Iqbal Pribadi (MANAJEMEN, 2025)
The transportation and logistics sector is a sector that plays a vital role as one of the main elements that has a great influence on economic development, comparable to production resources such as capital and labor. This study aims to analyze the effect of sales growth and debt to equity ratio on the financial performance of the transportation and logistics sector listed on the Indonesia Stock Exchange in 2014-2023. The data collection technique in this study uses a quantitative approach. The sample in this study was taken using a purposive sampling technique so that 90 research samples were obtained with a total of 9 companies. Data analysis techniques using multiple linear regression. The results of the study indicate that sales growth has a significant effect on financial performance and debt to equity ratio does not have a significant effect on financial performance.